SOCIO-SPATIAL DYNAMICS AND NEW TERRITORIAL CONFIGURATIONS: THE URBAN DYNAMICS OF RIDE - GRANDE TERESINA - Melo Filho, José Maria Marques de (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.926, 2020)
The transformations caused by the socio-spatial dynamism implies the emergence in the Brazilian urban network of new territorial configurations, such like: the metropolis, the scattered cities, the urban basins, the agglomerations urban, among others. Within that universe, the focus of analysis of this work was the so-called Integrated Economic Development Regions (RIDE), more specifically the RIDE - Grande Teresina. The purpose of the research is to analyze the urban dynamics of said arrangement, since it has characteristics different from those undertaken in metropolitan spaces. To reach our objective we base the discussions based on the following authors: Corrêa (2011); Lencioni (2011); Ferreira (2016); Moura (2012); Limonad (2007); Gurgel (2017); Egler (2010), among others. The studies done were also evaluated on the evolution of the Brazilian urban network, such as: IPEA (2002); IBGE (2008, 2013 and 2016) and Observatorio de las Metropolis (2004). Also, the results of the Integrated Region. We show that the urban evolution of the RIDE It presents an urban dynamic governed by the regional capital (Teresina) with a low integration between the federated entities that compose it, and also, highlights the divergence between the socio-spatial process and the institutional process of the RIDE.